Direct action of mineral fertilizers and optimum level of their application in Crop rotations depending on soddy-podsolic soils fertility in the western Polissya - Kotvytskyi, B.B. (AgroChemistry and Soil Science, 2016)
With long-term stationary field research in crop rotations in Ukrainian Western Polissya using methods of division of experimental plots and nitrogen (15N) of fertilizer it was defined direct action of fertilizers on crop rotation productivity; were calculated coefficients of nitrogen fertilizer use by winter rye and determined the effect of fertilizer systems on some properties of sod-podzolic sandy loam soil. According to the results of 40-year monitoring of different fertilizer systems, the optimal timing of their use in crop rotations were recommended.